DNA Methylation of the t-PA Gene Differs Between Various Immune Cell Subtypes Isolated From Depressed Patients Receiving Electroconvulsive Therapy - Moschny, Nicole; Jahn, Kirsten; Bajbouj, Malek; Maier, Hannah Benedictine; Ballmaier, Matthias; Khan, Abdul Qayyum; Pollak, Christoph; Bleich, Stefan; Frieling, Helge; Neyazi, Alexandra (Frontiers in Psychiatry, 2020)
Background Major Depressive Disorder (MDD) represents a tremendous health threat to the world’s population. Electroconvulsive therapy (ECT) is the most effective treatment option for refractory MDD patients. Ample evidence suggests brain-derived neurotrophic factor (BDNF) to play a crucial role in ECT´s mode of action. Tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) are involved in BDNF production. Hypothesis The DNA methylation of gene regions encoding for t-PA and PAI-1 might be a suitable biomarker for ECT response prediction. Methods We withdrew blood from two cohorts of treatment-resistant MDD patients receiving ECT. In the first cohort (n=59), blood was collected at baseline only. To evaluate DNA methylation changes throughout the treatment course, we acquired a second group (n=28) and took blood samples at multiple time points. DNA isolated from whole blood and defined immune cell subtypes (B cells, monocytes, natural killer cells, and T cells) served for epigenetic analyses. Results Mixed linear models (corrected for multiple testing by Sidak’s post-hoc test) revealed (1) no detectable baseline blood DNA methylation differences between ECT remitters (n=33) and non-remitters (n=53) in the regions analyzed, but (2) a significant difference in t-PA’s DNA methylation between the investigated immune cell subtypes instead (p<0.00001). This difference remained stable throughout the treatment course, showed no acute changes after ECT, and was independent of clinical remission. Conclusion DNA methylation of both proteins seems to play a minor role in ECT’s mechanisms. Generally, we recommend using defined immune cell subtypes (instead of whole blood only) for DNA methylation analyses.